The Power Dynamics of Sunda Wiwitan Traditional Leaders as Cultural Mediators in the Seren Taun Ceremony in Cigugur Village, Kuningan Regency - Umam, Irfan; Imawan, Khaerudin; Adiputra, Novicky (Interaction Communication Studies Journal, 2026)
This study aims to examine the cultural meanings, communication practices, power dynamics, and the role of actor networks in the Seren Taun ceremony in Cigugur Village, Kuningan Regency. A qualitative approach was employed, with data collected through in-depth interviews, participant observation, and documentation. The findings indicate that the cultural meanings of Seren Taun are conveyed through symbols, such as rice in the ngajayak procession, the Buyung Dance, Angklung Buncis, and the rice-pounding (nutu) ritual, which represent values of gratitude, social cohesion, balance in life, and the continuity of relationships between humans, nature, and the divine. Furthermore, the study reveals that traditional leaders play a central role as cultural communicators through verbal and nonverbal strategies. Verbal communication is expressed through traditional speeches that reinforce cultural values and authority, while nonverbal communication is reflected in exemplary actions and the involvement of the younger generation in ritual practices. From the perspective of power relations theory, the authority of traditional leaders operates symbolically and persuasively rather than coercively, enabling cultural values to be accepted and internalized by the community. In addition, Actor-Network Theory highlights that cultural meanings are produced through interactions between human actors such as traditional leaders and community members and non-human actors, including ritual symbols and artifacts. This interconnected network ensures the continuous reproduction and transmission of cultural values. Overall, the Seren Taun ceremony functions not only as a ritual tradition but also as a sustainable medium of cultural communication that maintains the identity and continuity of the Sunda Wiwitan community amid social change.